2015
DOI: 10.1002/adfm.201501760
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed Anatomical Nerve Regeneration Pathways

Abstract: An imaging-coupled 3D printing methodology for the design, optimization, and fabrication of a customized nerve repair technology for complex injuries is presented. The custom scaffolds are deterministically fabricated via a microextrusion printing principle which enables the simultaneous incorporation of anatomical geometries, biomimetic physical cues, and spatially controlled biochemical gradients in a one-pot 3D manufacturing approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
253
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 250 publications
(260 citation statements)
references
References 71 publications
1
253
0
Order By: Relevance
“…Using 3D printing technology, Johnson et al developed bifurcation nerve scaffolds with imbedded growth factor gradients for the first time, and demonstrated its therapeutic effect in a rat nerve regeneration model. 129 Our approach loaded path specific neurotrophic factors (NGF for axons and GDNF for Schwann cells) to promote selective regeneration of peripheral nerves, and in vivo results demonstrated that functional recovery was improved with these novel devices. 129 Yurie et al further confirmed in rats that 3D printed conduits promoted nerve regeneration.…”
Section: Fabricationmentioning
confidence: 92%
See 2 more Smart Citations
“…Using 3D printing technology, Johnson et al developed bifurcation nerve scaffolds with imbedded growth factor gradients for the first time, and demonstrated its therapeutic effect in a rat nerve regeneration model. 129 Our approach loaded path specific neurotrophic factors (NGF for axons and GDNF for Schwann cells) to promote selective regeneration of peripheral nerves, and in vivo results demonstrated that functional recovery was improved with these novel devices. 129 Yurie et al further confirmed in rats that 3D printed conduits promoted nerve regeneration.…”
Section: Fabricationmentioning
confidence: 92%
“…129 Our approach loaded path specific neurotrophic factors (NGF for axons and GDNF for Schwann cells) to promote selective regeneration of peripheral nerves, and in vivo results demonstrated that functional recovery was improved with these novel devices. 129 Yurie et al further confirmed in rats that 3D printed conduits promoted nerve regeneration. 130 Many reports have shown that 3D printing technology provides an exciting new fabrication technique that may be able to fulfill clinical needs for complicated and patient-specific artificial nerve grafts which cannot be satisfied by conventional fabrication techniques.…”
Section: Fabricationmentioning
confidence: 92%
See 1 more Smart Citation
“…We have described the methodology of CatWalk (Noldus Information Technology, The Netherlands) before [6,37,38]. Briefly, one week prior to surgery, animals were trained daily on a CatWalk runway until they were able to make consecutive uninterrupted runs.…”
Section: Methodsmentioning
confidence: 99%
“…Various strategies for improving nerve repair have been proposed in basic, pre-clinical and clinical trials [46]. Stem cell transplantation therapy has emerged as a particularly promising strategy to improve outcomes in pre-clinical models [79].…”
Section: Introductionmentioning
confidence: 99%